2013
DOI: 10.5688/ajpe77594
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Empathy Scale in Pharmacy and Nursing Students

Abstract: Objective. To validate an empathy scale to measure empathy in pharmacy and nursing students. Methods. A 15-item instrument comprised of the cognitive and affective empathy domains, was created. Each item was rated using a 7-point Likert scale, ranging from strongly disagree to strongly agree. Concurrent validity was demonstrated with the Jefferson Scale of Empathy -Health Professional Students (JSE-HPS).Results. Reliability analysis of data from 216 students (pharmacy, N5158; nursing, N558) showed that scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 36 publications
(48 reference statements)
1
87
0
1
Order By: Relevance
“…In this study, we provide evidence in support of reliability and construct validity of JSE-HPS for assessing empathy among Chinese pharmacy students. Cronbach's alpha coefficient in this study (0.81) was similar to those reported for American pharmacy students (0.80-0.84), 9,19 indicating that the JSE-HPS is internally consistent in Chinese pharmacy students. Factor analysis in Chinese pharmacy students showed a three-factor solution that was somewhat similar to the pattern that emerged from Hojat's original study 23 using the original JSPE on physicians.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…In this study, we provide evidence in support of reliability and construct validity of JSE-HPS for assessing empathy among Chinese pharmacy students. Cronbach's alpha coefficient in this study (0.81) was similar to those reported for American pharmacy students (0.80-0.84), 9,19 indicating that the JSE-HPS is internally consistent in Chinese pharmacy students. Factor analysis in Chinese pharmacy students showed a three-factor solution that was somewhat similar to the pattern that emerged from Hojat's original study 23 using the original JSPE on physicians.…”
Section: Discussionsupporting
confidence: 70%
“…9 firstly examined the validity and reliability of the JSE-HPS in 187 first-year pharmacy students at Midwestern University Chicago College of Pharmacy. 19 then showed that scores on the empathy scale were positively associated with JSE-HPS scores in 158 American pharmacy students. In this study, we provide evidence in support of reliability and construct validity of JSE-HPS for assessing empathy among Chinese pharmacy students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations